The Construction of the Other and the Self in André Gide's Travels in the Congo and Frantz Fanon's Black Skin, White Masks - Raphaël Lambert (Studies in 20th & 21st Century Literature, 2003)
Reportedly, André Gide's Travels in the Congo (1929) had fostered reforms of the colonial policy in French Africa. In Travels, Gide reports cases of economic exploitation, abuses of power, use of terror, torture, and even homicidal raids against recalcitrant villagers and, at least in one case, Gide takes it upon himself to have a man prosecuted. Yet his account, through the lense of post-colonial thinking, betrays reactionary and biased views of Africans. Gide does not object to the colonial system per se, but rather blames its malfunction on both a lack of infrastructures and administrative involvement. In Black Skin, White Masks (1952), Frantz Fanon denounces colonialism, focusing on its dehumanizing effects. If Fanon believes that it is the responsibility of those oppressed to regain their freedom, he is also aware that colonized people have internalized racial stereotypes to the point of self-loathing. Hence Black Skin can be read as a rebuttal to Travels. While Travels, published only twenty years earlier, clings to values of past centuries—supporting France's "civilizing" mission in Africa, Black Skin looks toward the future as it condemns the ideology of colonialism. Both liberals, communist sympathizers and social activists, Gide and Fanon represent the two opposite poles of the colonial issue.
Keywords: other; self; André Gide; travels in the Congo; colonialism; French Africa; violence; oppressed; freedom; racial stereotypes; Black skin; white masks